2003
DOI: 10.1007/s00296-003-0357-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in patients with rheumatoid arthritis

Abstract: Heart rate variability (HRV) is a useful tool for the detection of sympathetic-parasympathetic balance in the autonomic nervous system. Autonomic nervous system involvement in patients with rheumatoid arthritis (RA) has rarely been studied and has shown conflicting results. Our purpose was to determine if HRV showed changes in patients with RA in comparison with the normal population. Short-term analysis of HRV was performed for time-domain frequency in 42 patients with RA and 44 matched controls. In this anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
95
4
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 24 publications
5
95
4
9
Order By: Relevance
“…6 Statistical time domain measures like SDNN and RMSSD are indices of general autonomic balance. 7 In this study, mean HR, SBP and DBP were found significantly higher in all smokers than non smokers. Similar results were also found by Andrikopoulas et al and Cagirci et al in heavy smokers.…”
Section: Discussionmentioning
confidence: 64%
“…6 Statistical time domain measures like SDNN and RMSSD are indices of general autonomic balance. 7 In this study, mean HR, SBP and DBP were found significantly higher in all smokers than non smokers. Similar results were also found by Andrikopoulas et al and Cagirci et al in heavy smokers.…”
Section: Discussionmentioning
confidence: 64%
“…On the other hand, reduced HRV acts as a strong predictor of many cardiac diseases. 9 Time domain method determines the heart rate at any point in time or the intervals between successive normal QRS complex in a continuous ECG record. Common simple time domain variables include mean normal to normal QRS complex (NN) interval and the mean heart rate.…”
Section: Methodsmentioning
confidence: 99%
“…Onset may be at any age imbalance. [10][11][12] Though both peripheral and central nervous system involvement has been well recognized but information on involvement of autonomic nervous system is scarcely available. 10 Heart rate variability (HRV) reflects autonomic nervous control.…”
mentioning
confidence: 99%